Lactylated apolipoprotein C-II induces immunotherapy resistance by promoting extracellular lipolysis - Chen, Jian; Zhao, Deping; Wang, Yupeng; Liu, Ming; Zhang, Yuan; Feng, Tingting; Xiao, Chao; Song, Huan; Miao, Rui; Xu, Li; Chen, Hongwei; Qiu, Xiaoying; et al. (Advanced science, 2024)
Mortality rates due to lung cancer are high worldwide. Although PD-1 and PD-L1 immune checkpoint inhibitors boost the survival of patients with non-small-cell lung cancer (NSCLC), resistance often arises. The Warburg Effect, which causes lactate build-up and potential lysine-lactylation (Kla), links immune dysfunction to tumor metabolism. The role of non-histone Kla in tumor immune microenvironment and immunotherapy remains to be clarified. Here, global lactylome profiling and metabolomic analyses of samples from patients with NSCLC is conducted. By combining multi-omics analysis with in vitro and in vivo validation, that intracellular lactate promotes extracellular lipolysis through lactyl-APOC2 is revealed. Mechanistically, lactate enhances APOC2 lactylation at K70, stabilizing it and resulting in FFA release, regulatory T cell accumulation, immunotherapy resistance, and metastasis. Moreover, the anti-APOC2K70-lac antibody that sensitized anti-PD-1 therapy in vivo is developed. This findings highlight the potential of anti lactyl-APOC2-K70 approach as a new combination therapy for sensitizing immunotherapeutic responses.
Erstmals veröffentlicht: 09. Juli 2024
Gesehen am 18.11.2024